On the Orientalism and Neo-Orientalism in Ayad Akhtar’s Disgraced: Analysis on the Dynamics of Amir and Emily’s Relationship - Alyssa Syahmina Putri; Herlin Putri Indah Destari (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2019)
This study analyses the three essential elements of the interracial relationship between Amir and Emily in Ayad Akhtar’s Pulitzer Prize-winning play, Disgraced. They are: Emily’s painting of Amir, her husband, in the style of Portrait of Juan de Pareja by Diego Velázquez; Emily’s White Saviour Complex; and the violence she suffered in the hands of Amir. The first two parts of the analysis will utilise the combination of Identity Construction theory by Stuart Hall, Edward Said’s Orientalism, and the post 9/11 discourse of neo-Orientalism. The last part of the analysis will foreground the entire elements by utilising Stuart Hall’s theory of Articulation. It will be proved that Amir’s violence is an act of retaliation towards Emily’s domination over the production of his identity through representation and her influence in his crucial decisions concerning his relationship with his family. Emily’s victimisation and the emphasis on Amir’s ‘tribalistic bond’ risk a reductionist neo-Orientalist reading of the text. By acknowledging Emily’s White Saviour Complex, the text can be read as a re-articulation of the neo-Orientalist stereotypes of ‘barbaric brown man’ and ‘free white woman.’